Transformasi Panduan Tajwid pada Mushaf Al-Qur’an - Jonni Syatri (SUHUF, 2020)
This article is studying the phenomenon of changes in the way of presenting the guideline of tajwid (the rule of Qur’anic reading) in the Qur’an in Indonesia. The scope of the study is the guideline of tajwid contained in the mushaf which had been published since 1984 to 2020. The determination of the Indonesian Standard Qur’an was done in 1984, and then since that time, the Indonesian Standard Qur’an became the reference in the publication, printing and correction of the mushaf in Indonesia. The guideline of tajwid which becomes the focus of this study is in the form of text narration of the summary of tajwid being attached in the first section or in the end section of the mushaf, and the sign system presented directly in the Qur’anic text in the form of colored block, that of number and that of name of the rules of tajwid. This article is the library research presented by using analysis-descriptive approach. The result of the study shows that there is the transformation of the use of letters from the Arabic-Malay to the Latin letters. In addition to that, the form of presentation is also changed from the narrative pattern of the text in the form of the attachment in the mushaf to the system of sign presented in the text of the Qur’an.